Sucrose non-fermenting1-related protein kinase VcSnRK2.3 promotes anthocyanin biosynthesis in association with VcMYB1 in blueberry - Wang, Xuan; Tang, Qi; Chi, Fumei; Liu, Hongdi; Zhang, Hongjun; Song, Yang (Frontiers in Plant Science, 2023)
Sucrose non-fermenting1-related protein kinase-2 (SnRK2) is a plant-specific protein kinase family and an important component of the abscisic acid (ABA) signaling pathway. However, there is a lack of relevant studies in blueberry (Vaccinium corymbosum). In this study, we identified six SnRK2 family members (from VcSnRK2.1 to VcSnRK2.6) in blueberries for the first time. In addition, we found that VcSnRK2.3 expression was not only positively correlated with fruit ripening but was also induced by ABA signaling. Transient expression in blueberry fruits also proved that VcSnRK2.3 promoted anthocyanin accumulation and the expression of anthocyanin synthesis-related genes such as VcF3H, VcDFR, VcANS, and VcUFGT. Transgenic Arabidopsis thaliana seeds and seedlings overexpressing VcSnRK2.3 showed anthocyanin pigmentation. Yeast two-hybrid assays (Y2H) and Bimolecular fluorescence complementation assays (BiFC) demonstrated that VcSnRK2.3 could interact with the anthocyanin positive regulator VcMYB1. Finally, VcSnRK2.3 was able to enhance the binding of VcMYB1 to the VcDFR promoter. Via regulation transcription of anthocyanin biosynthesis genes, VcSnRK2.3 promoted anthocyanin accumulation in blueberry. The above results suggest that VcSnRK2.3 plays an important role in blueberry anthocyanin synthesis, is induced by ABA, and can interact with VcMYB1 to promote anthocyanin biosynthesis in blueberry.